HOW DOES TRADITIONAL HOME-GARDENS SUPPORT ETHNOMEDICINAL VALUES IN KUMAUN HIMALAYAN BHABHAR BELT, INDIA? - Padalia, Kirtika; Bargali, Kiran; Bargali, Surendra Singh (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Medicine is one of the four basic needs of human being fulfilled by the plant up to a large extent. Herbal remedies have been anintegrated part of healing and are considered to be the oldest form of healthcare known to mankind on this earth.Materials and methods: An ethno botanical survey has been conducted using semi structured interview schedule with the villagers, in agro forestrysystem to identify the traditionally used plants.Results: A total of 60 medicinal plants belonging to the 33 families were found to be used for the treatment of diseases. Out of 33 families,Cucurbitaceae contributed maximum 06 genera followed by Poaceae, Brassicaceae, Solanaceae and Apiaceae. The documented plants were listed as32 herbs, 06 shrubs, 15 trees and 07climbers. Different parts of investigated plants such as leaves (34%), fruits (19%), bark (only 2%) etc. wereuseful to cure the 10 different categories of ailments. In this study, about 70% of the medicines were prepared by fresh plant parts. The mode ofapplication of herbal medicines was oral (53.33%), dermal (10%) and rest (36.66%) taken both by oral and dermal.Conclusions: Indigenous people still believe in traditional system of medicine and prefer it in search of primary health care. Such plants may be usedin the formulation of new drugs. The agroforestry system supports the ethno-botanical values in a very extensive way. It is one of the best knowntraditional practices to cure and prevent the diseases from the very beginning of civilization, other than to full fill the daily requirement of food,fodder and timber production. The remedies obtained from the agroforestry and home gardens system are comparatively cheaper, pure, have no sideeffects and easily available. Therefore, it deals with those communities whom have the limited access to mainstream medicine. Agroforestry providesthe alternative source of remedies and growing space for medicinal plant. Hence, there is a great a need to cultivate and conserve such plants and atthe same time, there is an immediate need of indigenous practices, knowledge of such plant resources, and documentation.